Conditional Oprk1-dependent Kiss1 deletion in kisspeptin neurons caused estrogen-dependent LH pulse disruption and LH surge attenuation in female rats - Mayuko Nagae; Koki Yamada; Yuki Enomoto; Mari Kometani; Hitomi Tsuchida; Arvinda Panthee; Miku Nonogaki; Nao Matsunaga; Marina Takizawa; Sena Matsuzaki; Masumi Hirabayashi; Naoko Inoue; et al. (Scientific Reports, 2023)
Abstract The gonadotropin-releasing hormone (GnRH) pulse and surge are considered to be generated by arcuate kisspeptin/neurokinin B/dynorphin A (KNDy) neurons and anteroventral periventricular nucleus (AVPV) kisspeptin neurons, respectively, in female rodents. The majority of KNDy and AVPV kisspeptin neurons express κ-opioid receptors (KORs, encoded by Oprk1) in female rodents. Thus, this study aimed to investigate the effect of a conditional Oprk1-dependent Kiss1 deletion in kisspeptin neurons on the luteinizing hormone (LH) pulse/surge and fertility using Kiss1-floxed/Oprk1-Cre rats, in which Kiss1 was deleted in cells expressing or once expressed the Oprk1/Cre. The Kiss1-floxed/Oprk1-Cre female rats, with Kiss1 deleted in a majority of KNDy neurons, showed normal puberty while having a one-day longer estrous cycle and fewer pups than Kiss1-floxed controls. Notably, ovariectomized (OVX) Kiss1-floxed/Oprk1-Cre rats showed profound disruption of LH pulses in the presence of a diestrous level of estrogen but showed apparent LH pulses without estrogen treatment. Furthermore, Kiss1-floxed/Oprk1-Cre rats, with Kiss1 deleted in approximately half of AVPV kisspeptin neurons, showed a lower peak of the estrogen-induced LH surge than controls. These results suggest that arcuate and AVPV kisspeptin neurons expressing or having expressed Oprk1 have a role in maintaining normal GnRH pulse and surge generation, the normal length of the estrous cycle, and the normal offspring number in female rats.